A mudança da ordem dos constituintes adjetivo e substantivo na língua catalã: uma análise diacrônica (Revista de Estudos da Linguagem, 2004)
In face of the quantitative analysis of sintagma nominal (SN) of theCatalan language, giving relevance to the relations between theconstituents, adjective and substantive, and, through a corpuscomposed of texts dated from the 13th, 14th, 15th, and 20thcenturies, I noted the change of word order of the constituents A(adjective) and N (substantive), to AN > NA. In other words, theold order, the anteposition of A to N, gives place to a more recentform, the posposition of A in relation to N. I verified that certaininherent semantic features act as determinative factors of the orderof these constituents, the adjectives and substantives.